المشروع التشاركي للحوكمة الرشيدة في الجامعات التونسية: قراءة تقييمية نقدية - القابسى، منصف (جامعة الجزائر2 - أبو القاسم سعدالله, 2018)
يكشف مفهوم المسؤولية المجتمعية أن دور الجامعات عبر العالم لم يصيح يتأسس على وظيفتين رئيسيتين هما وظيفتا التعليم من ناحية والبحث العلمي من ناحية ثانية، بل انضافت وظيفة ثالثة هي المسؤولية الاجتماعية أو المسؤولية المدنية أو خدمة المجتمع. ومنذ أواخر القرن الماضي بدأت العديد من الجامعات العربية في الانخراط في الميثاق العالمي الذي يؤسس لهذا التمشي. إلا أن ضعف هذا الانخراط كان من بين الأسباب الذي جعل غالبية الجامعات في الوطن العربي، تقبع في ذيل في أكثر القياسات الدولية تداولا. وللتكيف مع هذا التطور لوظيفة الجامعات، طرح في بداية 2015 مشروع لإصلاح منظومة التعليم العالي والبحث العلمي في تونس، وشارك في صياغته أهم الفاعلين في الحقل الأكاديمي. وسنحاول في مقالتنا المساهمة في قراءة نقدية وتقييمية لهذا المشروع ولمختلف الرؤى التي تعاملت معه، ونبين إلى أي مدى يمكن اليوم الدفع بالجامعات التونسية إلى مزيد من الالتزام الاجتماعي والمدني.
The concept of corporate social responsibility is based on the idea that the work of the institutions, their functioning and the regularity of their mechanisms should not be limited to seeking financial profit and economic benefits, but should also take into account the interest of central actors in their environment. Applied to tertiary education a third function called, social responsibility, or civil liability or service to the community, has been added to the two classic functions of this sector which are teaching and scientific research. The weak commitment of Arab universities to the global charter that establishes this approach has been one of the reasons for their poor placement in the rankings of universities at the global level. In our article, we propose a critical and evaluative reading of the project launched in 2015 to reform the system of higher education and scientific research in Tunisia; In particular, we will be interested in the different points of view generated by its content and the possibilities recommended to bring Tunisian universities to a greater social and civic commitment.
Keywords: الإدارة التربوية -- حوكمة المؤسسات -- علم الاجتماع التربوي -- مؤسسات التعليم العالي -- تونس